Predicting kinetics of water-rich permeate flux through photocatalytic mesh under visible light illumination - Bishwash Shrestha; Mohammadamin Ezazi; Seyed Vahid Rad; Gibum Kwon (Scientific Reports, 2021)
Abstract Membrane-based separation technologies are attractive to remediating unconventional water sources, including brackish, industrial, and municipal wastewater, due to their versatility and relatively high energy efficiency. However, membrane fouling by dissolved or suspended organic substances remains a primary challenge which can result in an irreversible decline of the permeate flux. To overcome this, membranes have been incorporated with photocatalytic materials that can degrade these organic substances deposited on the surface upon light illumination. While such photocatalytic membranes have demonstrated that they can recover their inherent permeability, less information is known about the effect of photocatalysis on the kinetics of the permeate flux. In this work, a photocatalytic mesh that can selectively permeate water while repelling oil was fabricated by coating a mixture of nitrogen-doped TiO2 (N-TiO2) and perfluorosilane-grafted SiO2 (F-SiO2) nanoparticles on a stainless steel mesh. Utilizing the photocatalytic mesh, the time-dependent evolution of the water-rich permeate flux as a result of photocatalytic degradation of the oil was studied under the visible light illumination. A mathematical model was developed that can relate the photocatalytic degradation of the organic substances deposited on a mesh surface to the evolution of the permeate flux. This model was established by integrating the Langmuir–Hinshelwood kinetics for photocatalysis and the Cassie–Baxter wettability analysis on a chemically heterogeneous mesh surface into a permeate flux relation. Consequently, the time-dependent water-rich permeate flux values are compared with those predicted by using the model. It is found that the model can predict the evolution of the water-rich permeate flux with a goodness of fit of 0.92.